2015
DOI: 10.1021/jacs.5b11880
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Onset of Crystallinity in Ion-Containing Aqueous Nanodrops

Abstract: Water exhibits remarkable properties in confined spaces, such as nanometer-sized droplets where hundreds of water molecules are required for crystalline structure to form at low temperature due to surface effects. Here, we investigate how a single ion affects the crystallization of (H2O)n clusters with infrared photodissociation spectroscopy of size-selected La(3+)(H2O)n nanodrops containing up to 550 water molecules. Crystallization in the ion-containing nanodrops occurs at n ≥ 375, which is approximately 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
60
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(70 citation statements)
references
References 33 publications
9
60
0
1
Order By: Relevance
“…Indications for a water–ice phase transition for water clusters with 60–79 water molecules at 133 ± 6 K and for a phase transition to crystalline ice for La 3+ ·(H 2 O) 375 at 133 K have been reported previously. 6366 Therefore, our interpretation of the increased average water molecule binding enthalpies within a modified 133 K TLDM is consistent with these findings. With bulk ice parameters and optimizing γ and ∂ln( p / p 0 )/∂ T , the experimental values can be reproduced with accuracies of ±0.8 kJ mol –1 between n = 20–500 water molecules.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Indications for a water–ice phase transition for water clusters with 60–79 water molecules at 133 ± 6 K and for a phase transition to crystalline ice for La 3+ ·(H 2 O) 375 at 133 K have been reported previously. 6366 Therefore, our interpretation of the increased average water molecule binding enthalpies within a modified 133 K TLDM is consistent with these findings. With bulk ice parameters and optimizing γ and ∂ln( p / p 0 )/∂ T , the experimental values can be reproduced with accuracies of ±0.8 kJ mol –1 between n = 20–500 water molecules.…”
Section: Discussionsupporting
confidence: 87%
“…Evidence for the influence of ions on the water phase in large water clusters comes from a recent study that showed that La 3+ ions can affect the onset of crystallinity in clusters as large as 375 water molecules. 63 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These interactions are especially important in environments where water is scarce, such as in living cells and reverse micelles, and will manifest as changes to the dynamics of surrounding water molecules as well as freezing point depression. 40 Long-distance forces originating from ions may also partially account for Hofmeister and other ion-related phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Using IRPD spectroscopy of mass-selected, ion-containing water clusters, orientation effects on water by a single solvated ion free of any counterion contributions can be measured. 21,39,40 The sensitivity of this technique is not limited by the ratio of water molecules to ions. As a result, ion–water interactions can be measured to a hypothetical infinite dilution.…”
Section: Introductionmentioning
confidence: 99%